Using a massive high‐resolution ensemble climate data set to examine dynamic and thermodynamic aspects of heavy precipitation change. (4th August 2021) - Yamada, Tomohito J.; Hoshino, Tsuyoshi; Suzuki, Akihiro
Abstract: This study investigated the relationship between extreme precipitation and near‐surface temperature (precipitation–temperature relation) from two different perspectives, the rate of change of precipitation with temperature and dynamic (i.e., effect of the change in atmospheric motion) and thermodynamic (i.e., effect of the change in atmospheric moisture content) aspects, using a 5‐km dynamical downscaled hundreds‐year data set for past climate condition (PAST; from 1951 to 2010) and future climate condition (FUTURE; 4°C warmer than the preindustrial condition). Initially, using the observation and the PAST and FUTURE data sets, it was found that the 99th and 99.9th percentile hourly precipitation for each temperature bin ( P 99 and P 99.9, respectively) paralleled the slope of the Clausius–Clapeyron (C–C) relation for a certain temperature range over the Tokachi River basin in Hokkaido, the northern island of Japan; however, both P 99 and P 99.9 decreased in the high‐temperature range. Next, we examined the cause of the P 99 and P 99.9 differences between PAST and FUTURE for each temperature bin by classifying dynamic and thermodynamic factors. The result showed that the thermodynamic effect dominates the differences in P 99 and P 99.9 between PAST and FUTURE, which means that the thermodynamic effect is the main component of the precipitation–temperature relation. Similar analyses were applied to the whole river basin, including the mountainous area. The results showed that the differences in P 99 and P 99.9 between PAST and FUTURE are mainly due to the thermodynamic contribution, regardless of plain or mountain area. Using such large model data sets, we could make a robust assessment of the precipitation–temperature relation and the dynamic and thermodynamic contributions to precipitation changes. Moreover, using the 5‐km resolution hundreds‐year data set enabled us to quantify the spatial distribution of such precipitation characteristics over a thousands of square kilometer catchment. Abstract : This study investigated the relationship between extreme precipitation and near‐surface temperature from the rate of change of precipitation with temperature and dynamic and thermodynamic aspects, using a 5‐km resolution hundreds‐year dataset. The extreme hourly precipitation for each temperature bin paralleled the Clausius–Clapeyron relation (7% per ℃) in many areas over the Tokachi River basin, Hokkaido, Japan and the differences between past and future climate are mainly due to the thermodynamic contribution, regardless of plain or mountain area.